Learning to Export and Learning by Exporting: The Case of East Java Manufacturing Industry - Rizqi Qurniawan; Shania Rahmi (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
The manufacturing industry contribution and its proportion to the exports in recent years has become dominant in supporting the East Java Province economy. Previous literature showed the impact of export participation in increasing a firm’s productivity. Meanwhile, little literature explains how the manufacturing industry learns about the benefits of exports so that it leads to an increase in a firm’s productivity. Using a large and medium industrial panel dataset from 2008 to 2015 in East Java Province, this study found that export participation in the manufacturing industry significantly increases a firm’s productivity. This increased productivity is due to the selectivity of productivity because manufacturing firms experience learning to export. In addition, this study also found that the manufacturing industry in East Java experienced learning by exporting even with a short duration since entering the export market. By knowing the learning scheme of export participation in the manufacturing industry in East Java, policy recommendations can be established, such as export promotion strategies, export market expansion, and decreased export costs so that the manufacturing industry can increase productivity.